DAYA TERIMA COOKIES KALENYONG (TEPUNG KACANG MERAH, TEPUNG IKAN LELE DAN TEPUNG GANYONG) SEBAGAI SELINGAN TINGGI FE UNTUK REMAJA PUTRI ANEMIA - Cherina Cherina; Yuli Hartati; Nurul Salasa Nilawati (Journal of Nutrition College, 2026)
ABSTRACTBackground: Iron deficiency anemia is a prevalent nutritional problem in Indonesia, including in Muara Enim Regency (5.72%). This condition affects immunity, activity, and learning performance of adolescent girls. The Government's iron supplementation program (Iron tablets) has been sub-optimal due to low compliance. Therefore, an alternative in the form of highly acceptable iron-rich snacks is needed. Cookies made from red bean flour (Fe 5.2 mg/100g), catfish flour (Fe 5.3 g/100g), and canna flour (Fe 3.3 mg/100g) were developed as an innovative solution.Objectives: : To determine the best formulation of Kalenyong cookies, analyzing the differences in the acceptability of 3 biscuit formulas including color, aroma, texture and taste), as well as testing the proximate content and iron content of the best selected formula.Methods: This pure experimental research used completely randomized design (CRD) conducted from January to May 2025. Data were analyzed using Kruskal- Wallis test and Mann-Whitney post hoc test.Results : The selected formula (F3) with composition of red bean flour 100 g, catfish flour 90 g, and canna flour 60 g showed highest organoleptic scores (color 3.90; taste 3.90; aroma 4.10; texture 3.97; aftertaste 3.87). Nutritional content per 100 g: energy 499.17 kcal, protein 20.12 g, fat 14.17 g, carbohydrate 80.53 g, water content 6.43%, ash 1.39%, and iron 8.49 mg.Conclusion:  There were significant differences (p<0.05) in Cookies acceptability regarding color, aroma, texture, taste, and aftertaste. Kalenyong Cookies have potential as high-Fe snack for anemic adolescent girls.Keywords : Cookiefs; catfish flour; canna flour;red bean flour;anemia ABSTRAKLatar belakang: Anemia defisiensi besi merupakan masalah gizi yang prevalensinya tinggi di Indonesia, termasuk di Kabupaten Muara Enim (5,72%). Kondisi ini berdampak pada penurunan imunitas, aktivitas, dan prestasi belajar remaja putri. Pemberian tablet tambah darah (TTD) sebagai intervensi pemerintah belum optimal akibat rendahnya kepatuhan. Oleh karena itu, diperlukan alternatif berupa makanan selingan tinggi zat besi yang lebih diterima. Cookies berbahan tepung kacang merah (Fe 5,2 mg/100 g), tepung ikan lele (Fe 5,3 mg/100 g), dan tepung ganyong (Fe 3,3 mg/100 g) dikembangkan sebagai solusi inovatif.Tujuan: Menentukan formulasi terbaik Cookies Kalenyong, menganalisis perbedaan daya terima 3 formula biskuit yang meliputi warna, aroma, tekstur dan rasa), serta menguji kandungan proksimat dan kadar zat besinya dari formula terbaik yang terpilih.Metode: Penelitian eksperimental murni dengan rancangan acak lengkap (RAL) dilakukan pada Januari–Mei 2025. Analisis data menggunakan uji Kruskal-Wallis dan uji lanjut Mann-Whitney dari 3 formula.Hasil: Formula terpilih (F3) dengan komposisi tepung kacang merah 100 g, tepung ikan lele 90 g, dan tepung ganyong 60 g memiliki skor organoleptik tertinggi (warna 3,90; rasa 3,90; aroma 4,10; tekstur 3,97; aftertaste 3,87). Kandungan per 100 g: energi 499,17 kkal, protein 20,12 g, lemak 14,17 g, karbohidrat 80,53 g, kadar air 6,43%, abu 1,39%, dan zat besi 8,49 mg.Simpulan: Terdapat perbedaan signifikan (p<0,05) pada daya terima Cookies dari segi warna, aroma, tekstur, rasa, dan aftertaste. Cookies Kalenyong berpotensi sebagai selingan tinggi Fe untuk remaja putri anemia.Kata Kunci: Cookies; tepung kacang merah; tepung ikan lele; tepung ganyong; anemia